Cost-effectiveness and Safety of Interspinous Process Decompression (Superion) - Cairns, Kevin (Pain Med, 2019)
OBJECTIVE: There are several treatment options for patients suffering from lumbar spinal stenosis, including surgical and conservative care. Interspinous spacer decompression using the Superion device offers a less invasive procedure for patients who fail conservative treatment before traditional decompression surgery. This review assesses the current cost-effectiveness, safety, and performance of lumbar spinal stenosis treatment modalities compared with the Superion interspinous spacer procedure. METHODS: EMBASE and PubMed were searched to find studies reporting on the cost-effectiveness, safety, and performance of conservative treatment, including medicinal treatments, epidural injections, physical therapy, and alternative methods, as well as surgical treatment, including laminectomy, laminectomy with fusion, and interspinous spacer decompression. Results were supplemented with manual searches. RESULTS: Despite substantial costs, persistent conservative treatment (>12 weeks) of lumbar spinal stenosis showed only minimal improvement in pain and functionality. When conservative treatment fails, surgery is more effective than continuing conservative treatment. Lumbar laminectomy with fusion has considerably greater cost than laminectomy alone, as the length of hospital stay increases, the costs for implants are substantial, and complications increase. Although laminectomy and the Superion have comparable outcomes, the Superion implant is positioned percutaneously. This approach may minimize the direct and indirect costs of outpatient rehabilitation and absenteeism, respectively. CONCLUSIONS: Superion interspinous lumbar decompression is a minimally invasive procedure for patients with lumbar spinal stenosis who have failed conservative treatment. Compared with extending conservative treatment or traditional spinal surgery, interspinous lumbar decompression reduces the direct and indirect costs associated with lumbar spinal stenosis.